Molecular epidemiology of cystic fibrosis mutations and haplotypes in southern Italy evaluated with an improved semiautomated robotic procedure. Issue 6 (June 1996) - Castaldo, G; Rippa, E; Sebastio, G; Raia, V; Ercolini, P; de Ritis, G; Salvatore, D; Salvatore, F
Abstract : We screened for 22 cystic fibrosis (CF) mutations in DNA from a first cohort of 69 CF patients from southern Italy using a semiautomated allele specific oligonucleotide (ASO) dot blot procedure based on two multiplex PCR amplifications. Seven mutations (delta F508, N1303K, G542X, 1717-1 G–>A, W1282X, 1148T, and R553X) identified 77.6% of CF chromosomes. Detection reached 79.8% with the 2183 AA–>G mutation analysed with the restriction generating PCR method. Thus, we included the 2183 AA–>G mutation in the ASO protocol and set up the conditions to amplify the gene regions that include the eight mutations in a single multiplex PCR reaction. With this method we tested the DNA of the first cohort of 69 CF patients, a second cohort of 63 CF patients, and 300 carrier relatives; we also performed 12 prenatal diagnoses. The results from the 132 CF patients showed differences in the distribution of CF mutations between the south and north of Italy. The XV2c, KM19, and intron 8 VNDR haplotypes suggested the presence, in CF chromosomes bearing undetected mutations, of a limited number of unknown mutations typical of southern Italy. Finally, for six of the eight mutations, we compared the ASO procedure with the methods based on restriction enzymes; the results obtained with the two procedures were identical for all the 57 chromosomes compared.